Impact of acute kidney injury in elderly versus young deceased donors on post-transplant outcomes: A multicenter cohort study - Park, Woo Yeong (Sci Rep, 2020)
We investigated the impact of acute kidney injury (AKI) in elderly deceased-donors (DDs) vs. AKI in young DDs on post-transplant clinical outcomes. A total of 709 kidney transplant recipients (KTRs) from 602 DDs at four transplant centers were enrolled. KTRs were divided into young-DDKT and elderly-DDKT groups according to the age of DD of 60 years. Both groups were subdivided into non-AKI-KT and AKI-KT subgroups according to AKI in DDs. We investigated short-term and long-term clinical outcomes of non-AKI-DDKT and AKI-DDKT subgroups within young-DDKT and elderly-DDKT groups. The incidence of DGF in the AKI-DDKT subgroup was higher and the allograft function within 12 months after KT in the AKI-DDKT subgroup was lower than those in the non-AKI-DDKT subgroup in both young-DDKT and elderly-DDKT groups. Death-censored allograft survival rate was significantly lower in the AKI-elderly-DDKT subgroup than that in the non-AKI-elderly-DDKT subgroup, but it did not differ between AKI-young-DDKT and non-AKI-young-DDKT subgroup. In multivariable analysis, AKI-elderly-DDKT was an independent risk factor for allograft failure (hazard ratio: 2.648, 95% CI: 1.170–5.994, p = 0.019) and a significant interaction between AKI and old age in DDs on allograft failure was observed (p = 0.001). AKI in elderly DDs, but not in young DDs, can significantly affect long-term allograft outcomes of KTRs.